Urotensin-II, oxidative stress, and inflammation increase in hypertensive and resistant hypertensive patients. (3rd April 2021) - Guler, Eray Metin; Gokce, Mustafa; Bacaksiz, Ahmet; Kocyigit, Abdurrahim
ABSTRACT: Objective : Hypertension is a multi-factorial process prevalent in developed as well as in developing countries. Urotensin-II, different antioxidants, free radicals, and inflammatory biomarkers play an essential role in the cardiovascular system. The aim of this study is to investigate Urotensin-II, oxidative stress, and inflammation markers in normotensive, hypertensive, and resistant hypertensive patients. Methods : Fifty resistance hypertensive (rHT) patients, 50 hypertensive patients, and 50 age gender matched normotensive controls (NT-control) were enrolled. Urotensin-II (UII), total oxidant status (TOS), total antioxidant status (TAS), native thiol (NT), total thiol (TT), disulfide (DIS), interleukin 1 beta (IL1β), interleukin 6 (IL6), tumor necrosis factor-alpha (TNFα), high sensitive c reactive protein (hsCRP), high-density lipoprotein (HDL) low-density lipoprotein (LDL), and total cholesterol (TC) were evaluated. Results : Serum levels of UII, IL1β, IL6, TNFα, DIS, TOS, and OSI were found higher in rHT and HT as compared to NT-control ( p < .001). On the contrary, serum levels of TT, TAS, and NT were lower in rHT and HT as compared to NT-control ( p < .001). While TC, hsCRP, TOS, OSI, UII, IL1β, IL6, and TNFα levels increase from HT to rHT group ( p < .001); TAS and NT levels decrease from HT to rHT group ( p < .001). Conclusions : UII levels, oxidative stress, and inflammation are higher in rHT and HT, while antioxidants and thiol levels are lower than the NT-control. Our study clearly showed that rHT and HT are more susceptible to impaired states of antioxidants, oxidative stress, and free radicals.